Some Aspects of French Railway War Finance - Howard, Stanley E. (Quarterly Journal of Economics, 1918)
Provisions of the agreements of 1883, 309. — Distinction between statutory interest and dividends, 311. — Terms of state's guaranty of earnings, 312. — Results for the Eastern, P. & 0., and Southern companies up to 1914, 316. — Results since 1914, 319. — Results for the Northern and P. L. M. companies up to 1914, 321. — Results for the same companies since 1914, 321. — Measures of relief suggested for the Eastern and Northern lines, 324. — Proposal for advance of rates on all roads, 327.